Biomechanical Analysis of Smash Movement in Badminton Athletes: A Case Study - M Arrival Mahindra M Arrival Mahindra; Riska Mulya Riska Mulya; Radja Bumi Dirgantara Radja Bumi Dirgantara; A’mal Nazhif Daulay A’mal Nazhif Daulay; Tifan Fradous Sihombing Tifan Fradous Sihombing; Mahmudin Matondang Mahmudin Matondang (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to analyze the biomechanical aspects of the smash movement of a university-level badminton athlete using a case study methodology. The smash is one of the most important strokes in badminton, as it primarily functions as an attacking stroke that is expected to directly generate points. The effectiveness of the smash is greatly influenced by coordination between body segments, movement speed, and joint angles used in each phase of the movement. The subject of this study was a university student badminton athlete with four years of training experience. Data was obtained through high-speed video recording (120 fps) and analyzed using Kinovea software to measure joint angles, swing speed, and the shuttlecock's trajectory. The results showed that in the preparation phase, the knee angle was around 110°, which functions as a potential energy support, while the elbow angle was around 80° in preparation for the arm swing. In the swing phase, shoulder rotation reaches high speeds that contribute to the acceleration of the stroke. Upon contact with the shuttlecock, the wrist angle opens approximately 25° to increase power. However, weaknesses were found in the follow-through phase where the foot position is less balanced, reducing the accuracy of the stroke. The results of this study emphasize the importance of body segment coordination and core stability training in supporting smash effectiveness.